Double Core-Hole Generation in O2 Molecules Using an X-Ray Free-Electron Laser: Molecular-Frame Photoelectron Angular Distributions - Kastirke, Gregor; Schöffler, Markus S.; Weller, Miriam; Rist, Jonas; Boll, Rebecca; Anders, Nils; Baumann, Thomas M.; Eckart, Sebastian; Erk, Benjamin; De Fanis, Alberto; Fehre, Kilian; Gatton, Averell; et al. (My University, 2020)
We report on a multiparticle coincidence experiment performed at the European X-ray Free-Electron Laser at the Small Quantum Systems instrument using a COLTRIMS reaction microscope. By measuring two ions and two electrons in coincidence, we investigate double core-hole generation in O2 molecules in the gas phase. Single-site and two-site double core holes have been identified and their molecular-frame electron angular distributions have been obtained for a breakup of the oxygen molecule into two doubly charged ions. The measured distributions are compared to results of calculations performed within the frozen- and relaxed-core Hartree-Fock approximations.